Kinetics and Characterization of Degradation Products of Dihydralazine and Hydrochlorothiazide in Binary Mixture by HPLC-UV, LC-DAD and LC–MS Methods - Gumieniczek, Anna (Chromatographia, 2018)
Dihydralazine and hydrochlorothiazide were stored at high temperature and humidity, under UV/Vis light and different pH, as individual drugs and the mixture. Then, a sensitive and selective HPLC-UV method was developed for simultaneous determination of dihydralazine and hydrochlorothiazide in presence of their degradation products. Finally, the degradation products were characterized through LC-DAD and LC–MS methods. Dihydralazine was sensitive to high temperature and humidity, UV/Vis light and pH ≥ 7. At the same time, it was resistant to acidic conditions. Hydrochlorothiazide was sensitive to high temperature and humidity, UV/Vis light and changes in pH. Its highest level of degradation was observed in 1 M HCl. Degradation of the drugs was higher when they were stressed in the mixture. In the case of dihydralazine, the percentage degradation was 5–15 times higher. What is more, dihydralazine became sensitive to acidic conditions. Hydrochlorothiazide was shown to be more sensitive to UV/Vis light and pH > 4. Degradation of dihydralazine and hydrochlorothiazide followed first-order kinetics. The quickest degradation of dihydralazine was found to be in 1 M NaOH while of hydrochlorothiazide was in 1 M HCl (individual hydrochlorothiazide) or at pH 7–10 (hydrochlorothiazide in the mixture). A number of new degradation products were detected and some of them were identified by our LC-DAD and LC–MS methods. In the stressed individual samples, (phenylmethyl)hydrazine and 1,2,4-benzothiadiazine-7-sulfonamide 1,1-dioxide were observed for the first time. Interactions between dihydralazine and hydrochlorothiazide in the mixture were confirmed by additional degradation products, e.g., 2H-1,2,4-benzothiadiazine-7-sulfonamide 1,1,4-trioxide.